Characterization of Adsorbent Developed from Rice Husk: Effect of Surface Functional Group on Phenol Adsorption - Daffalla, S.B.; H., Mukhtar; Shaharun, Maizatul Shima (2010)
Over the last three decades, there has been increasing global concern over the public health impacts attributed to environmental pollution. Among various water pollutants, phenol and its derivatives are the most toxic because they are carcinogenic in nature. The objective of this study was to develop novel, low-cost adsorbent from rice husk modified by thermal and chemical treatments for the effective removal of phenol from industrial wastewater. The physical and surface properties of the developed adsorbents were characterized using FTIR, SEM and FSEM. The results indicated that the pretreatment of rice husk has caused the functional groups (-OH, Si-OH, C-H, C=O, C=C, CH2, CH3, CO, Si-O-Si, C-C, Si-H, -O-CH3) on the surface of adsorbent to change and the specific surface area to increase. The adsorption capacity was greatly influenced by surface group changes. The effects of the presence of the surface functional group on adsorption of phenol were analyzed by observing the shifting of the FTIR peaks after the adsorption experiment. Analysis of FTIR shows that the -OH, C-H,-CO, C-OH, Si-OH and -Si-H groups contribute to the adsorption of phenol onto the surface of adsorbent.